Mini Review: Effect of GLP-1 Receptor Agonists and SGLT-2 Inhibitors on the Growth Hormone/IGF Axis - Cignarelli, Angelo; Genchi, Valentina Annamaria; Le Grazie, Giulia; Caruso, Irene; Marrano, Nicola; Biondi, Giuseppina; D’Oria, Rossella; Sorice, Gian Pio; Natalicchio, Annalisa; Perrini, Sebastio; Laviola, Luigi; Giorgino, Francesco (Frontiers in Endocrinology, 2022)
Accumulating evidence supports the early use of glucagon-like peptide-1 receptor agonists (GLP-1RAs) and sodium glucose transporter-2 inhibitors (SGLT-2is) for the treatment of type 2 diabetes. Indeed, these compounds exert numerous pleiotropic actions that favourably affect metabolism and diabetes comorbidities, showing an additional effect beyond glucose control. Although a substantial amount of knowledge has been generated regarding the mechanism of action of both drug classes, much remains to be understood. Growth hormone (GH) is an important driver for multiple endocrine responses involving changes in glucose and lipid metabolism, and affects several tissues and organs (e.g., bone, heart). It acts directly on several target tissues, including skeletal muscle and bone, but several effects are mediated indirectly by circulating (liver-derived) or locally produced IGF-1. In consideration of the multiple metabolic and cardiovascular effects seen in subjects treated with GLP-1RAs and SGLT-2is (e.g., reduction of hyperglycemia, weight loss, free/fat mass and bone remodelling, anti-atherosclerosis, natriuresis), it is reasonable to speculate that GH and IGF-1 may play a about a relevant role in this context. This narrative mini-review aims to describe the involvement of the GH/IGF-1/IGF-1R axis in either mediating or responding to the effects of each of the two drug classes.